When a negative (charge) is not a positive: sialylation and its role in cancer mechanics and progression - Habeeb, Issa Funsho; Alao, Toheeb Eniola; Delgado, Daniella; Buffone, Alexander (Frontiers in Oncology, 2024)
Sialic acids and sialoglycans are critical actors in cancer progression and metastasis. These terminal sugar residues on glycoproteins and glycolipids modulate key cellular processes such as immune evasion, cell adhesion, and migration. Aberrant sialylation is driven by overexpression of sialyltransferases, resulting in hypersialylation on cancer cell surfaces as well as enhancing tumor aggressiveness. Sialylated glycans alter the structure of the glycocalyx, a protective barrier that fosters cancer cell detachment, migration, and invasion. This bulky glycocalyx also increases membrane tension, promoting integrin clustering and downstream signaling pathways that drive cell proliferation and metastasis. They play a critical role in immune evasion by binding to Siglecs, inhibitory receptors on immune cells, which transmit signals that protect cancer cells from immune-mediated destruction. Targeting sialylation pathways presents a promising therapeutic opportunity to understand the complex roles of sialic acids and sialoglycans in cancer mechanics and progression, which is crucial for developing novel diagnostic and therapeutic strategies that can disrupt these processes and improve cancer treatment outcomes.